Updating the neurodevelopmental profile of Alazami syndrome: Illustrating the role of developmental assessment in rare genetic disorders. Issue 8 (10th May 2019) - Wojcik, Monica H.; Linnea, Kate; Stoler, Joan M.; Rappaport, Leonard
Abstract: Alazami syndrome, caused by biallelic pathogenic variants in LARP7, is a recently‐described rare genetic disorder, with 17 patients currently reported in the literature. We present a case of a male infant referred for genetics evaluation at 5 months of age, found at 17 months of age to have Alazami syndrome. He was promptly referred for developmental evaluation, where he was found to be higher functioning than prior reports of individuals with this condition. This demonstrates the neurodevelopmental phenotypic variability seen in rare genetic disorders; it also demonstrates the important role of developmental programs to measure and track outcomes and provide support for infants with genetic disorders that put them at risk of developmental disabilities.